People, forests, and change : lessons from the Pacific Northwest - Olson, Deanna H.; Van Horne, Beatrice (Island Press, 2017)
Forests throughout the world are undergoing rapid, far-reaching change as a result of natural and anthropogenic disturbances. The challenge is to manage these ests in ways that avoid formulaic approaches to complex issues. This book takes on the challenge of balancing local economies, wood products, and biodiversity by proposing diverse new approaches to forest management using new research from the moist coniferous forests of the Pacific Northwest.- Resumé vydavatel
Keywords: lesy -- Spojené státy americké (severozápadní oblast); lesnictví -- Spojené státy americké (severozápadní oblast); udržitelné lesní hospodářství -- Spojené státy americké (severozápadní oblast); forests -- United States, Northwestern; forestry -- United States, Northwestern; sustainable forest management -- United States, Northwestern; elektronické knihy; sborníky; electronic books; papers of several authors